Chemical Changes in Strained Dairy Product Produced with Organic Milk by Using Kefir Grains and Yogurt Culture during Refrigerated Storage - Guler, Zehra; Tekin, Ali; Dursun, Ahmet (Sidas Medya A.S., 2019)
The objective of this study was to produce a strained dairy product made from organic milk using yogurt culture and kefir grains as a new product development. Strained dairy product was analyzed for carbohydrates, organic acids, volatile organic compounds (VOCs), basic chemical composition as well as overall acceptability at 1, 7, 14, 21 and 28 days of refrigerated storage. While galactose content in dairy products increased, lactose and glucose contents decreased on 14th day of storage. The main VOC was ethanol, accounted for about 58% of total volatiles. An increase in succinic acid (from 312 mg/kg to 638 mg/kg), acetic acid (632 mg/kg-843 mg/kg), ethyl octanoate (1.07%-4.15%) and a decrease in viscosity (5754 mPas-1050 mPas) and total solids (24.33%-20.64%) towards the end of storage were observed. Refrigerated storage for more than 21 days could not be recommended since the product was found unacceptable by the panelists but the product consumption at the first 21 days of storage may be an advantage for lactose intolerance humans due to its low lactose level. © 2019 Authors. All rights reserved.
Kefir Tanesi ve Yoğurt Kültürü ile Organik Sütten Üretilen Süzme Süt Ürününün Soğuk Depolanması Sırasında Kimyasal Değişimler
Keywords: Kefir; Organic acids; Strained dairy product; Volatile organic compounds; Yogurt